Analysis Of Factors Affecting Medication Adherence Among Hypertension Patients At The Primary Clinic Polkes 01.10.02 Lubuk Pakam In 2025 - Indriani, Restutri; Rifai, Achmad; Ate, Keleng (JURNAL KESMAS DAN GIZI (JKG), 2025)
This research explores the determinants of adherence to antihypertensive medication among patients at the Primary Care Clinic Polkes 01.10.02 Lubuk Pakam. Hypertension refers to a consistent elevation in blood pressure, typically above 140/90 mmHg. Clinical records indicated a growing number of hypertension cases: 1,001 in 2021, 1,115 in 2022, and 1,074 in 2023. The highest recovery rate was recorded in 2022, with 1,056 patients showing improvement after undergoing treatment. A quantitative approach was adopted, utilizing an analytical survey with a cross-sectional design. A total of 95 hypertension patients were selected purposively from the Pegasing Health Center. Data analysis included univariate, bivariate, and multivariate techniques. The study identified significant associations between medication adherence and several factors: level of education (p = 0.000), patient knowledge (p = 0.000), distance to healthcare facilities (p = 0.000), family involvement (p = 0.000), length of time on medication (p = 0.000), and health education received (p = 0.005). Among these, the duration of medication use emerged as the most influential factor (p = 0.017; 95% CI = 2.088–1614.65). The findings suggest that these six factors play a critical role in patients' consistency with hypertension therapy. Strengthening healthcare personnel's involvement and implementing strategic interventions is advised to enhance adherence and lower hypertension rates